Understanding hedonic and utilitarian responses to product reviews on youtube and purchase intention - Pantas H. Silaban; Andri Dayarana K. Silalahi; Edgar Octoyuda; Yuni Kartika Sitanggang; Lamtiur Hutabarat; Ade Irma Suryani Sitorus (Cogent Business & Management, 2022)
YouTube has become popular among consumers as an information preference in the decision-making process within the social commerce environment. YouTubers share experiences, information, opinions, and thoughts regarding products or services in product-review content, and consumers' motivations (hedonic or utilitarian) in reacting to how the content affect their buying behavior. This study investigates hedonic and utilitarian consumer responses to YouTubers' product reviews that lead to purchase intention. We employed a questionnaire data collection method targeted at consumers who buy products after watching product-review content on YouTube. We collected 384 valid responses and employed structural equation modeling to test the validity and research hypotheses. The results showed that (1) parasocial interaction significantly influences hedonic (transparency, perceived enjoyment) and utilitarian (credibility, informativeness) responses and purchase intention, while (2) hedonic (perceived transparency) and utilitarian (informativeness) responses were insignificant for purchase intention. In addition, hedonic (perceived enjoyment) and utilitarian (credibility) responses have significant effects on purchase intention. Thus, YouTubers' product-review content on YouTube influences consumer behavior in both hedonic and utilitarian terms. While marketers implement marketing strategies to include products in YouTube content, YouTubers communicate products to consumers. Furthermore, the theoretical and practical contributions of this study are discussed.
Keywords: 650; Hedonic and Utilitarian; Online Consumer Behavior; Parasocial Interaction; Purchase Intention; Social Media Marketing; YouTube; YouTubers